La question alimentaire dans l’action publique locale. Analyse croisée des trajectoires municipales de Paris et de Brive-la-Gaillarde - Sabine Bognon; Pauline Marty (VertigO)
In the early 20th century, a centralized regime featured urban food systems in France, and the public and urban spheres governed it. Since the 1950s, urban food supply has become a trade issue, left to the opaque management of private stakeholders and ad minima regulated by public authorities. More recently, since the 2000s, the food system and its agro-industrial logics are questioned, through individual or collective initiatives, including by public action, enlighten by the sustainable development issues. How, within almost a century, can we tell and analyze the trajectory of urban food systems ? And specifically, how the place of the local public action in the governance of food flow was first ousted and seems now to return through food supply relocation initiatives ? Answers to these questions are suggested with the analysis of two French cases : one in Paris, the capital city, a stronghold of important and specific consumption, and the other in Brive-la-Gaillarde, medium town set in a rural area, featured by its shipments of agricultural products on a regional and national market. We provide a cross-analysis of two contemporary municipal policies involving reterritorialisation of the urban food supply, concerning street markets in Paris and school catering in Brive. We aim at identifying the potential and proven impacts of these and innovative initiatives on the recent trajectory of the urban supply.